The identity politics of Elfquest at 40: moving beyond race, class and gender?. Issue 1 (2nd January 2019) - Saunders, Robert A.
ABSTRACT: This article provides a critical analysis of the political content of Wendy and Richard Pinis' independent comic series Elfquest (1978–present), focusing on the identity triad of race, class and gender. In my analysis of Elfquest (EQ) as a popular culture-based political intervention, I make a threefold contribution to the literature of popular geopolitics. First, in a normative contribution challenging the norms of male-dominated 1970s-era comics, I situate EQ as subversive medium that imagined a new world ordered by the progressive values of the '1968 generation'. Second, via a theoretical contribution, I present EQ fandom as a form of transformative political engagement, wherein the reader/seer maps their own situatedness in the US's changing socio-political milieu. And, third, in an empirical contribution, I provide a critical analysis of the original series, interrogating Elfquest 's engagement with identity politics through a close reading of the visuals and text of the 'Original Quest' (Issues #1–21, 1978–1984), fan feedback (letters to the editor), and interviews with the creators (including my own, conducted in 2017). In the conclusion, I reflect on EQ's transition to the post-identity politics of the contemporary era as the series concludes its fourth decade in publication.